Rapid detection of cytotoxicity of food additives and contaminants by a novel cytotoxicity test, menadione-catalyzed H(2)O(2) production assay - Yamashoji, Shiro (Kluwer Academic Publishers, 2001)
Menadione-catalyzed H(2)O(2) production by viable animal cells was proportional to the viable cell number, and H(2)O(2) production decreased with increasing cytotoxic effects after the incubation of cells with cytotoxic compounds. The cytotoxic effects of food additives, pesticides, antibiotics, heavy metals, phytotoxins, mycotoxins, and marine toxins were estimated using the above test employingNIH/3T3 and Neuro-2a cells. Synergistic effects of the toxin mixture were observed and acute cytotoxicity detected 1 h after the incubation of cells with toxins. This menadione-catalyzed H(2)O(2)production assay is rapid and simple compared to other popular cytotoxicity tests such as the MTT reduction assay and Neutral red inclusion test, requiring4 h. The menadione-catalyzed H(2)O(2) production assay is expected to be a useful food safety test for rapidly detecting toxic compounds having a basic cytotoxic effect on common animal cells.